In-depth analysis of culturable microalgae diversity in the river Nile at different locations - Badr, Amal Abouel-Fetouh (AUC Knowledge Fountain, 2020)
Identifying microalgae diversity in an ecosystem is essential not only to understand their impact on the ecosystem but also to recognize their potential in various applications that benefit humankind. The great biodiversity of microalgae and their ability to survive in drastic environmental by modifying their apparent phenotypes and cellular compositions has led to the continuous need for the development and modification of the current microalgae identification methods. This study evaluates the current culture-based identification method using two commonly used media (BG-11 and BBM) and the assessment of two modified media (MM) and a plant media (MS) to identify microalgae diversity from an environmental sample from the River Nile morphologically and molecularly. Moreover, the strengths and limitations of the two DNA-barcodes used (16S and 18S ribosomal RNA), and three reference databases in the identification of microalgae were evaluated. Through the modified culture-based method and media enrichment, a range of 30-34 microalgae species were morphologically identified in the Cairo samples. While, if only the two commonly used media have been used, 20-26 microalgae genera would have been morphologically identified. The molecular identification further aided in the identification of 70-78 microalgae in total to the genus level. Furthermore, by applying the four media types enrichment method, the River Nile microalgae culturable diversity in Upper Egypt and Cairo was investigated. This method aided in the identification of 35 genera in Cairo, 31 genera in El-Menya, 21 genera in Asyut, 21 genera in Sohag, 16 genera in Luxor and Aswan, 20 genera in KIMA and 21 genera in Lake Nasser. Our results show that the use of one or two culture media to assess the diversity of environmental samples could result in the underestimation of microalgae diversity, and the MM media has potential in the identification of more species compared to the standard BG11 and BBM media. Similarly, the usage of one DNA marker or limiting the identification to one database would result in the underestimation of microalgae diversity. This study also is important and sheds light on the fact that regular microalgae diversity analysis in the River Nile is essential to maintain the aquatic ecosystem and to preserve the vital microalgae that holds great potential impact in terms of industry and medicine.